THE UNIQUENESS THEOREM FOR HYDROGEN ATOM EQUATION - Bas, Erdal; Panakhov, Etibar; Yilmazer, Resat (Inst Applied Mathematics, 2013)
In this article, we prove that the difference between two potential functions becomes sufficiently small whenever the spectrums are chosen sufficiently close to each other.
Keywords: Sturm-Liouville problem; spectrum; asymptotic formula; norming constants; hydrogen atom